MOLECULAR GENETIC ANALYSIS OF INTERLEUKIN 4 GENE POLYMORPHISM AMONG TELEUTIANS, SHORIANS, AND CAUCASIANS IN KEMEROVO REGION - A. V. Ostaptseva; A. V. Shabaldin; V. R. Akhmatianova; V. I. Minina; A. N. Glushkov; V. G. Druzhinin; I. V. Zorkoltseva; E. V. Shabaldin; O. A. Glushkova; O. S. Makarchenko; T. N. Ageeva (Медицинская иммунология, 2014)
Abstract. An interleukin 4 polymorphism has been studied in Teleutians, Shorians, and Caucasoids living in the Kemerovo Region. The groups of Teleutians and Caucasoids are characterised with even or close-to-even distribution of the IL-4 alleles. The most widespread genotype in populations of Teleutians and Caucasoids was the 2R/3R heterozygosity, and 3R/3R proved to be the mostly rare. These data are indicative for mixing processes among Teleutians in the Kemerovo Region and Siberian Caucasoids. The major IL-4 genotype in Shorian population was 3R/3R, and the heterozygotic genotype 2R/3R took the second position.